2020
DOI: 10.3390/molecules25030518
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Methods for the Determination of Anthocyanins in Physiological Fluids via UHPLC-MSn

Abstract: Recent in vitro and in vivo studies on anthocyanins confirmed numerous health-promoting effects in humans. Daily anthocyanin intake can be estimated via food databases, but the amount absorbed by the organism still remains uncertain because anthocyanin bioavailability is yet to be elucidated in its entirety. For this purpose, suitable and validated methods of sample preparation and analysis are required. Therefore, a sample preparation method for anthocyanin metabolite analysis in plasma was successfully estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The presence of microbial catabolites at many sites of the body, at higher concentration than the native form, has suggested that part of the biological activities attributed to anthocyanins is related to the synergetic effect of their colonic catabolites [13,84]. Anthocyanin metabolites and transformation products have been characterized and quantified by several authors [85][86][87][88][89]. Ferrars et al [88] identified a wide variety of anthocyanin phenolic metabolites, including 11 novel metabolites, in post-menopausal women after 12 weeks elderberry intake, at concentration levels higher than their anthocyanin native forms.…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 99%
“…The presence of microbial catabolites at many sites of the body, at higher concentration than the native form, has suggested that part of the biological activities attributed to anthocyanins is related to the synergetic effect of their colonic catabolites [13,84]. Anthocyanin metabolites and transformation products have been characterized and quantified by several authors [85][86][87][88][89]. Ferrars et al [88] identified a wide variety of anthocyanin phenolic metabolites, including 11 novel metabolites, in post-menopausal women after 12 weeks elderberry intake, at concentration levels higher than their anthocyanin native forms.…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 99%
“…The repeatability of the technique is represented by the values of standard deviation, coefficient of variation, and confidence interval ( Table 2 ) [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The repeatability of the technique is represented by the values of standard deviation, coefficient of variation, and confidence interval (Table 2) [50,51]. Based on the assessment of the repeatability parameter, the intermediate precision studies were carried out.…”
Section: Repeatabilitymentioning
confidence: 99%
“…Samples were prepared according to a previously published protocol [ 26 ]. Briefly, 5 mL of a urine sample was evaporated at 40 °C under nitrogen flow to a final volume of 500–700 µL.…”
Section: Methodsmentioning
confidence: 99%